2015
DOI: 10.1111/tri.12679
|View full text |Cite
|
Sign up to set email alerts
|

10 years of prophylaxis with nebulized liposomal amphotericin B and the changing epidemiology ofAspergillusspp. infection in lung transplantation

Abstract: Summary The aim of this study was to assess the outcome and tolerability of prophylactic nebulized liposomal amphotericin B (n‐LAB) in lung transplant recipients (LTR) and the changing epidemiology of Aspergillus spp. infection and colonization. We performed an observational study including consecutive LTR recipients (2003–2013) undergoing n‐LAB prophylaxis lifetime. A total of 412 patients were included (mean postoperative follow‐up 2.56 years; IQR 1.01–4.65). Fifty‐three (12.8%) patients developed 59 Aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 37 publications
1
94
2
1
Order By: Relevance
“…infection (25). In our study, no statistical association was found, probably because of a statistical limitation related to a low incidence of aspergillosis secondary to an effective antifungal prophylaxis regimen (26).…”
Section: Discussioncontrasting
confidence: 63%
“…infection (25). In our study, no statistical association was found, probably because of a statistical limitation related to a low incidence of aspergillosis secondary to an effective antifungal prophylaxis regimen (26).…”
Section: Discussioncontrasting
confidence: 63%
“…Accepting that at least small conidial Aspergillus colonization is a risk factor for subsequent CLAD, what can be done to reduce this risk? The use of life-long inhaled Ambisome has reduced the risk of both colonization and subsequent CLAD derived from Aspergillus in one study [51]. However, this was not definitively demonstrated in their study, in part because we do not know if in their pre-Ambisome era Aspergillus colonization was a risk factor for CLAD.…”
Section: Aspergillus and Cladmentioning
confidence: 89%
“…Contrary to the above studies, Peghin [51] recently published their single-center experience with life-long inhaled Ambisome prophylaxis against invasive fungal disease and did not find that Aspergillus colonization was a risk factor for CLAD in the over 400 LTR followed. Quite the opposite, they found that CLAD was a risk for Aspergillus colonization or infection (HR 24.4, CI .…”
Section: Aspergillus and Cladmentioning
confidence: 91%
“…We read with interest the paper by Peghin et al [1] presenting the largest observational study on nebulized liposomal amphotericin B (n-LAB) as prophylaxis of aspergillosis in lung transplantation (LT). These authors adopted a lifelong approach with n-LAB administered at fixed dosage and frequency during the first 6 months and tapered thereafter.…”
Section: Dear Editorsmentioning
confidence: 99%